Harvester ants as ecological engineers for Mediterranean grassland restoration: Impacts on soil and vegetation. (May 2020) - De Almeida, Tania; Blight, Olivier; Mesléard, François; Bulot, Adeline; Provost, Erick; Dutoit, Thierry
Abstract: Although not widely used, ecosystem engineers represent a promising and sustainable tool in nature-based ecosystem management and restoration. In grassland ecosystems, a few invertebrates that engineer soils have been identified as key species regulating soil nutrients and plant communities' diversity and dynamics. Here, we assessed the role of the harvester ant Messor barbarus, an ecological engineer, in a Mediterranean dry grassland under restoration by characterising its nest environment, particularly the soil and vegetation. We found profound differences in soil physical and chemical variables and plant community structure between nests and ant-free patches in the restored grassland. Messor barbarus has improved soil fertility, driven the seed bank towards the reference grassland and significantly increased plant biomass, species richness and micro-local-heterogeneity. As biological filters, M . barbarus has driven plant communities towards a new trajectory in the restored site. Ant patches are characterised by mesotrophic species, whereas ant-free patches are dominated by species characteristic of compacted soils. They have accelerated the ecological recovery of Mediterranean dry grassland plants by directly and indirectly facilitating their re-establishment. These results illustrate the potential key role of ants as ecological engineers for the conservation and restoration of Mediterranean grasslands. Highlights: Ecosystem engineers may increase restoration success. Impacts of ants were studied seven years after soil replacement. Ants nests are characterised by higher soil fertility in the restored site. Ants have accelerated the ecological recovery of Mediterranean dry grasslands plants. Potential key role of ants as ecosystem engineers for the management of Mediterranean dry grasslands.